Social Stratification in Cinderella Movie (2015) - admin, admin (English Literature Department, Adab and Humanities Faculty, 2024)
This research has discussed social stratification in Cinderella (2015), a film from Walt Disney Studios. The researcher is interested in talking about all players in social class and the effects that are mirrored in the Cinderella movie. This movie doesn't only stick to the storyline of the fairy tale. Because of this, the author is interested in researching this film because ordinary people, when watching it, only focus on the love story. The aim of this research is to determine the social class and the effects that arise from that social class. To answer the problem formulation, the author uses the theory by Max Weber (2010) about social stratification. The researcher uses qualitative research and descriptive methods to achieve the research objectives. In collecting the data, the researcher has used documentation techniques. The findings of this research are: first, the researcher discovered several types of social classes, namely upper class, middle class, and lower class, and second, the effects that the author found, namely social relationships, employment, and crime.